Beam-shaping via femtosecond laser-modified optical fibre end faces - Ioannou, Athanasios; Michael, Polis; Lacraz, Amédéé; Theodosiou, Antreas; Kalli, Kyriacos (My University, 2016)
We present the results of investigations regarding laser micro-structuring of single mode optical fibres by direct access of the fibre end face and compare this with inscription in planar samples. We combine a high numerical aperture objective and femtosecond laser radiation at visible wavelengths to examine the spatial limits of direct writing and structuring at the surface of the optical fibre. We realise a number of interesting devices from one-and two-dimensional grating structures, to Bessel, Airy and vortex beam generators. We show the versatility of this simple but effective inscription method, where we demonstrate classic multiple slit diffraction patterns and patterns for non-diffracting beams, confirming that the flexible direct write method using femtosecond lasers can be to produce binary masks that can lead to beam shaping using a method that is applicable to all types of planar samples and through fine control of laser parameters to multi-mode and singlemode optical fibres.
Keywords: Diffraction grating; Femtosecond laser inscription; Non-diffracting optics; Optical vortex